Edukasi Tentang Zero Tolerance Kekerasan Seksual Pada Masyarakat Sekitar Kampus ITB - Wikaningtyas, Pratiwi; Soemari, Herlien Dwiarti; Damajanti, Irma; Damayanti, Sylviana Maya; Purwaningrum, Rr. Diah Asih; Danial, Danial; Rupiani, Dewi; Handayani, Fanty; Hidavat, Agustini; Nugroho, Edwin Adi; Salsabilla, Zahra; Putri, Gaitsa Farah Zahira; Karenina, Melita Jenar; Tinton S, Bonifacius Perdana (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2025)
In alignment with the mandate of the Ministerial Regulation of Education, Culture, Research, and Technology (Permendikbudristek) No. 30 of 2021 on the Prevention and Handling of Sexual Violence (PPKS) and ITB's Strategic Plan for continuous transformation to achieve national and global recognition, this community service initiative is designed to establish a zero-tolerance policy toward sexual harassment. Sexual harassment is a significant barrier to achieving educational goals; therefore, more rigorous efforts are needed to disseminate anti-sexual violence awareness from the university to external stakeholders surrounding the campus environment, such as vendors, café owners, boarding house managers, online motorcycle taxi drivers, and students. The socialization given by PPKS task force team for those audiences. These output include publications in mass media, pocketbooks, and stickers. Among the 156 participants who attended, the largest proportion comprised students (46.2%; n=72), followed by campus business operators (45.5%; n=71), café managers (6.4%; n=10), boarding house managers (1.3%; n=2), and online drivers (0.6%; n=1). It is expected the collaborative involvement of all stakeholders will strengthen efforts to prevent sexual violence within the campus environment.